Analysis of Teacher Needs in Developing Flipbook-Based Interactive Teaching Materials in Elementary Schools - Nafiah, Nafiah; Wuryandani, Wuri (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This research analyzes teachers' needs in developing flipbook-based interactive teaching materials in elementary schools. This research method uses quantitative research with a survey research type and descriptive qualitative. The research locations were Sidosermo 1 Surabaya public Elementary School, Margorejo VI public Elementary School Surabaya, Margorejo 1 public Elementary School, Taquma Elementary School, Kyai Ibrahim Elementary School, and Jemursari I Surabaya public elementary school. Data collection techniques using questionnaires. The research instrument is a wide questionnaire that experts have validated. Data analysis techniques were carried out using descriptive statistics and descriptive qualitative using data reduction, data display, and verification. The research results show that 100% of teachers need flipbook-based interactive teaching materials for elementary school students. This teaching material is considered the most appropriate and effective solution for meeting the learning needs of Pancasila Education in class IV, semester 2. The implications of these findings are significant. The demand for such teaching materials underscores the necessity of providing resources that are not only aligned with the curriculum but also capable of captivating students' interest and facilitating a deeper understanding of the content. Modern, interactive materials like flipbooks can offer a more dynamic learning environment, helping students better grasp complex concepts through engaging and visually stimulating content.